2019
DOI: 10.1016/j.cgh.2018.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Response to Vedolizumab and Ability of Dose Intensification to Restore Response in Patients With Crohn’s Disease or Ulcerative Colitis: A Systematic Review and Meta-analysis

Abstract: In a systematic review and meta-analysis, we found high proportions of patients with CD or UC to lose responsiveness to vedolizumab maintenance therapy. Dose intensification restores responsiveness to more than half of these patients. Additional studies are warranted to inform clinical decision making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
98
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 129 publications
(113 citation statements)
references
References 42 publications
11
98
0
4
Order By: Relevance
“…With low immunogenicity, and lack of clear data on target levels for mechanistic efficacy, the role of vedolizumab TDM in decision‐making (dose‐escalation or switching therapies) is adjunctive, and would require accounting for multiple clinical factors besides trough concentration. In a systematic review of 10 cohorts, pooled incidence rates of loss of response were 47.9 per 100 person‐years of follow‐up among patients with Crohn's disease and 39.8 per 100 person‐years of follow‐up in patients with ulcerative colitis; dose intensification was able to response to the drug in 53.8% patients with secondary nonresponders; TDM was not routinely performed in these cohorts . Since these data were not blinded or controlled data, it is possible that magnitude of benefit with empiric dose escalation may be overestimated; pivotal GEMINI trials did not identify any difference in efficacy of every 4 vs every 8 week dosing of vedolizumab.…”
Section: Discussionmentioning
confidence: 99%
“…With low immunogenicity, and lack of clear data on target levels for mechanistic efficacy, the role of vedolizumab TDM in decision‐making (dose‐escalation or switching therapies) is adjunctive, and would require accounting for multiple clinical factors besides trough concentration. In a systematic review of 10 cohorts, pooled incidence rates of loss of response were 47.9 per 100 person‐years of follow‐up among patients with Crohn's disease and 39.8 per 100 person‐years of follow‐up in patients with ulcerative colitis; dose intensification was able to response to the drug in 53.8% patients with secondary nonresponders; TDM was not routinely performed in these cohorts . Since these data were not blinded or controlled data, it is possible that magnitude of benefit with empiric dose escalation may be overestimated; pivotal GEMINI trials did not identify any difference in efficacy of every 4 vs every 8 week dosing of vedolizumab.…”
Section: Discussionmentioning
confidence: 99%
“…For anti‐TNF drugs, primary and secondary nonresponse rates in patients with IBD have been reported to be 10–30% and 20–40%, respectively . Although real‐life data for the newer anti‐integrin and anti‐interleukin drugs is limited and quite variable, similar nonresponse rates as for the anti‐TNF drugs have been observed …”
Section: Therapeutic Drug Monitoringmentioning
confidence: 82%
“…Nevertheless, a significant proportion of patients show an inadequate response to these agents during the induction, while others may even relapse after an initial response . Recent data from a systematic review showed estimated pooled incidence rates of LOR to VDZ of 47.9 and 39.8 per 100 person‐years of follow‐up (95% CI, 26.3‐87.0) in patients with CD and UC, respectively . This fact appears to be progressive during the maintenance phase, with cumulative rates of 20% and 35% at 6 and 12 months, respectively, showing slightly lower rates in CD than in UC (15% vs 18% at 6 months and 30% vs 39% at 12 months, respectively; P = .03) .…”
Section: Discussionmentioning
confidence: 99%
“…This fact appears to be progressive during the maintenance phase, with cumulative rates of 20% and 35% at 6 and 12 months, respectively, showing slightly lower rates in CD than in UC (15% vs 18% at 6 months and 30% vs 39% at 12 months, respectively; P = .03) . In this setting, the strategy of VDZ intensification may restore the response to the drug, but only in around half (54%) of secondary nonresponders . This clinical scenario raises an important question concerning the medical options for patients with UC refractory to anti‐integrin therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation